ANALISIS STRUKTUR BENTUK MUSIK LAGU “BLESSINGS’ LAURA MIXON STORY ELVINGTON - Novita Febriani; Dwi sutrianto; Epifani Omega (JURNAL PENABIBLOS, 2024)
This study aims to analyze the musical structure and lyrical meaning of Laura Story's song "Blessings." The primary challenge is understanding the complex and diverse music, which varies in form and style. The in-depth analysis includes melody, harmony, rhythm, tempo, dynamics, and instruments, as well as exploring the spiritual and theological messages in the lyrics. Using a qualitative approach, this research explains the musical structure and lyrical meaning of the song through hermeneutic and semantic methods. The song is divided into three main sections (A, B, C) with questions and answers in each section, forming a thematic development. The main conclusion of this study is that a deep understanding of the musical structure and lyrical context is essential for interpreting the emotional and spiritual depth of this song. This research contributes to the understanding of spiritual music and emphasizes the importance of God's blessings in musical expression.